Theoretical and practical aspects of pedagogy and psychology - Moskatova A. K., Gordeeva E. N., Lavina T. A., Zakharova A. N., Gritskevich T. I., Goriachevskaia E. V., Safonova M. V., Levchenko V. V., Lapshova E. S., Meshechkina R. P., Vysochinenko A. S., Ustinova E. M., Shilenko S. I., Zaritskaia V. V., Dzokaeva Z. M., Pavliuchenok M. B., Uliankova N. A., Sokolova G. A., Genvareva I. A., Marchenkova N. G., Leont'eva L. N., Sudakov O. V., Sudakov D. V., Belov E. V., Gordeeva O. I., Kretinina L. V., Sorokoumova G. V., Mychko E. I., Strelnikova E. S., Kumaeva M. V., Bulat R. E., Sharipova A. P. (Theoretical and practical aspects of pedagogy and psychology, 2022)
in the chapter describes the experience of prevention of maladaptation of first-year students, including the diagnosis of personality traits, identification of students at risk and psycho-corrective measures. The introduction substantiates the relevance of the problem of effective adaptation and prevention of maladaptation of first-year students, the importance of creating targeted systematic work with first-year students to prevent maladaptation. Materials and methods of research. In order to identify the risk group of students for various types of maladaptation and develop recommendations to reduce the level of maladaptation in first-year students, we conducted diagnostics of the personal characteristics of first-year students using the method of multifactorial personality research SMIL L.N. Sobchik Results and discussion of the results of the study. Based on the results of psychodiagnostics, we have developed recommendations for the risk group for hyposthenic /depressive type of maladjustment and for the risk group for the type of maladjustment «autism», including individual consultations, the inclusion of students in groups of psychological trainings on relevant topics, consultations for teachers and curators of groups on individual approach in interaction with students at risk, participation students in the work of a psychological circle in order to improve the psychological culture of students, etc. Conclusions. The work done made it possible to reduce the percentage of maladaptation of students and increase the efficiency of adaptation of first-year students to the process of studying at the university, which manifested itself in a significant decrease in the percentage of students expelled by the result of the 1st year of study.
Keywords: психологические тренинги; adaptation to university education; prevention of maladaptation; diagnosis of personality traits; psychological trainings; individual consultations; адаптация к обучению в вузе; профилактика дезадаптации; диагностика личностных особенностей; индивидуальные консультации